STRATEGI KOMUNIKASI PEMERINTAH KABUPATEN KONAWE DALAM PEMBANGUNAN PARIWISATA PANTAI TORONIPA - Narwasty, Mega Alma; Wiloso, Pamerdi Giri; Sasongko, Gatot (Universitas Kristen Satya Wacana, 2021)
This study examines the communication strategy designed by the Konawe district government. The design of the communication strategy aims to invite all people to be actively involved in collaborating with the local government in efforts to develop the Toronipa Beach tourism area. The research method used is a qualitative descriptive research approach as a methodological basis, while the data collection techniques are observation, in-depth interviews, and literature review. The communication strategy is analyzed using the communication strategy theory which states that the communication strategy is a combination of all communication elements consisting of message sources, messages, media, recipients, and also communication effects designed to achieve optimal communication goals. Based on the results of the research, it is known that the communication strategy carried out by the government involves the Chairperson of the LPM and Pokdarwis, the content of the communication message is an invitation to participate and information related to tourism development, deliberation forums as a medium of communication, different aspects review in communicant analysis, and organizational and participatory communication as the communication patterns. With this communication strategy, the government hopes that community participation will continue to increase and contribute to the development and management of Toronipa beach.